Allergic diseases and asthma in pregnancy, a secondary publication - Pali-Schöll, Isabella (World Allergy Organ J, 2017)
Every fifth pregnant woman is affected by allergies, especially rhinitis and asthma. Allergic symptoms existing before pregnancy may be either attenuated, or equally often promoted through pregnancy. Optimal allergy and asthma diagnosis and management during pregnancy is vital to ensure the welfare of mother and baby. For allergy diagnosis in pregnancy, preferentially anamnestic investigation as well as in vitro testing should be applied, whereas skin testing or provocation tests should be postponed until after birth. Pregnant women with confirmed allergy should avoid exposure to, or consumption of the offending allergen. Allergen immunotherapy should not be initiated during pregnancy. In patients on immunotherapy since before pregnancy, maintenance treatment may be continued, but the allergen dose should not be increased further. Applicable medications for asthma, rhinitis or skin symptoms in pregnancy are discussed and listed. In conclusion, i) allergies in pregnancy should preferentially be diagnosed in vitro; ii) AIT may be continued, but not started, and symptomatic medications must be carefully selected; iii) management of asthma and allergic diseases is important during pregnancy for welfare of mother and child.